Gender Authorship Trends of Review Articles in the Ophthalmology Literature from 2000 to 2022. - Özcan, Delil (Cyprus Journal of Medical Sciences, 2025)
BACKGROUND/AIMS To determine the gender distribution of authors and the change in this distribution between 2000 and 2022 in review articles published in the ophthalmology literature. MATERIALS AND METHODS The PubMed database was scanned using "Review", "Systematic Review", and "Meta-Analysis" as filters. Articles published in 71 major ophthalmology journals between 2000 and 2022 were included in the study. Genders of the first and last authors, and the countries of their institutions were extracted using the gender application program interface (https://gender-api.com) and MATLAB data analysis software. RESULTS A total of 16,711 review articles were published from 2000-2022, and 64,419 authors were evaluated within the scope of our study. Of these, 5,578 (33.4%) first authors and 4,081 (24.5%) last authors were female. In 2000, 8.6% of first authors and 6.0% of last authors were women. By 2022, this percentage had increased to 39.8% and 30.6%, respectively. The increasing trends in the rate of females becoming both first and last authors were statistically significant, and the difference between the slopes of the regression curves by analysis of covariance was so as well (R=0.861, p<0.001 for first authors and R=0.781, p<0.001 for last authors, respectively). In addition, there was a significant relationship between the gender identity of the first and last authors (p<0.001). CONCLUSION Our study reveals a trend towards resolving gender inequality in the field of ophthalmology. This novel finding is encouraging; however, we believe these developments are insufficient. Keywords:Gender, gender disparity, authorship, ophthalmology, review: